2016
DOI: 10.1002/syn.21914
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of buprenorphine analgesia by a combination of traditional and truncated mu opioid receptor splice variants

Abstract: Buprenorphine has long been classified as a mu analgesic, although its high affinity for other opioid receptor classes and the orphanin FQ/nociceptin ORL1 receptor may contribute to its other actions. The current studies confirmed a mu mechanism for buprenorphine analgesia, implicating several subsets of mu receptor splice variants. Buprenorphine analgesia depended upon the expression of both exon 1-associated traditional full length 7 transmembrane (7TM) and exon 11-associated truncated 6 transmembrane (6TM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 56 publications
1
41
0
1
Order By: Relevance
“…These findings support the idea 14 that opioid agonists with a strong bias towards G-protein-mediated signalling will retain their analgesic properties, but produce fewer side effects than unbiased opioids. Several laboratories have since identified G-protein-biased µOR agonists 4,[15][16][17][18][19] , many of which clearly separate analgesia from adverse side effects. One of these compounds, known as TRV130, is currently in phase III clinical trials 16 .…”
Section: Strategy For Making Safer Opioids Bolsteredmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings support the idea 14 that opioid agonists with a strong bias towards G-protein-mediated signalling will retain their analgesic properties, but produce fewer side effects than unbiased opioids. Several laboratories have since identified G-protein-biased µOR agonists 4,[15][16][17][18][19] , many of which clearly separate analgesia from adverse side effects. One of these compounds, known as TRV130, is currently in phase III clinical trials 16 .…”
Section: Strategy For Making Safer Opioids Bolsteredmentioning
confidence: 99%
“…This key parameter enumerates the increase in Earth's average surface temperature that would occur if atmospheric carbon dioxide concentrations were doubled and the climate system was given enough time to reach an equilibrium state. More than 150 estimates of equilibrium climate sensitivity (ECS) have been published 3 , many of which suggest that worryingly high sensitivities are possible -including one that was published in Nature just a few weeks ago 4 . On page 319, Cox et al 5 use an ingenious approach to rule out high estimates.…”
Section: P I E R S F O R St E Rmentioning
confidence: 99%
“…Although the analgesic action of BPN is mediated via MOR agonism and modulated by KOR, delta opioid receptors and nociceptin/orphanin FQ (N/OFQ) receptors (Lutfy et al, 2003), pharmacological and genetic blockade of opioid receptors confirmed that MORs alone are necessary for the analgesic properties of BPN (Grinnell et al, 2016; Ide et al, 2004). In the present studies, we demonstrate that the antinociceptive effects of BPN are dependent on the Oprm1 A112G SNP.…”
Section: Discussionmentioning
confidence: 99%
“…Analgesia produced by other compounds is significantly attenuated or completely absent in E11 KO mice (Majumdar et al 2011; Marrone et al 2016; Pan et al 2009). For example, buprenorphine analgesia was dependent upon both 6TM and 7TM variants (Grinnell et al 2016), as were morphine-6β-glucuronide and fentanyl, while IBNtxA analgesia was mediated only by 6TM ones (Majumdar et al 2011). 6TM variants also contribute to non-mu opioid analgesia (Marrone et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, morphine analgesia is unaffected by the selective elimination of 6TM variants in the E11 KO mouse (Pan et al 2009). However, the activity of other analgesics is dependent upon 6TM variants, such as buprenorphine (Grinnell et al 2016). Morphine also produces hyperalgesia that can become manifest after its analgesic actions wane.…”
Section: Introductionmentioning
confidence: 99%